العلاج بإستخدام الخلايا الجذعية: دراسة فقهية مقارنة - كرطي, فاطمة الزهراء (University of Eloued جامعة الوادي, 2019)
This research treats one of the important subjects in the domain of medical and life sciences, and which has a large practical applications; where he addressed the legitimacy border and controls for the stem cells therapy which is one of the cataclysms of medical Fiqh in this time, including some of the scientific aspects of this type of therapy and some of the provisions of the jurisprudential issues resulting from the exercise of this therapeutic method. The research tried to indicate the extent of the legality to benefit from the stem cells in therapy, and also indicate the legitimacy controls that governs this act. The important findings and recommendations result from this research that the legality of stem cells therapy is the base but with taking into account each medical cases and with legitimacy controls.
كتاب. إصدارات مخبر الدراسات الفقهية والقضائية. جامعة الوادي
Keywords: الخلايا الجذعية، العلاج، الأحكام، الفقه، ضوابط الشرعية; stem cells; therapy; provisions; medicine; legitimacy controls.